Students’ Difficulties and Strategies in Writing Essay at Ma’soem University - Rafi, Ilham (Jurnal Dimamu, 2025)
Essay is writing activities for practice or exercise, such as composing sentence with their knowledge. The purpose of this study focuses on students’ difficulties and the strategies to overcome the difficulties faced in writing essay at Masoem University.  To collect the data, a questionnaire adapted from was distributed to all of 4th semester students and semi-structured interview was addressed to nine participants. The questionnarie from contains various difficulties in essay writing process that include prewriting, coherence, cohesion, lexical and mechanic difficulties. The interview guideline from was employed to collect data regarding strategies used by students in overcoming their difficulties in essay writing.  The results show that the most difficulties is occur in mechanic, it can solved with five strategies such as making outline, find the appropriate resources, drafting, pause and reading, edit and revising. The implication of this research is useful for students as guideline for essay making, and for lecturer to make essay subject more complex